Orlando - Woolf, Virginia (Wordsworth Editions Ltd, 1995)
A story of a young man named Orlando, born in England, briefly a lover to the elderly queen followed by an intense love affair with a foreign princess whose sudden departure leaves him heartbroken. Orlando resorts to writing his poem The Oak Tree, started and abandoned in his youth. He finishes the poem only after mysterious transformation into a woman - the same person, with the same personality and intellect, but in a woman's body. A semi-biographical novel based in part on the life of Woolf's lover Vita Sackville-West.
Keywords: Fiction; General, Classic